Preparation method of all-solid-state battery
By using SIBS as the binder, the problems of electrode volume expansion and poor interface during charging and discharging of all-solid-state batteries are solved, and high cycle stability and environmentally friendly all-solid-state batteries are achieved, with a capacity retention rate of more than 85%.
Patent Information
- Application Number
- CN202411343682.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
During the charging and discharging process, all-solid-state batteries face problems such as expansion of electrode material volume and poor interface contact, resulting in poor circulation performance and shortened service life. Traditional dry adhesives have a great impact on the environment.
Using poly(styrene-b-isobutylene-b-styrene) triblock copolymer (SIBS) as the binder, prepare electrode sheets and electrolyte membranes to ensure the stability of the electrode during charging and discharging, and to the electrolyte High ionic conductivity is maintained in the membrane.
The cycle stability of all solid state batteries is significantly improved, the capacity retention rate of 200 cycles of charge and discharge cycle exceeds 80%, and the SIBS material is environmentally friendly, with high elasticity and good ion conduction properties.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a method for preparing an all-solid-state battery. Background Art
[0002] All-solid-state batteries are considered an important direction for the next generation of energy storage technology due to their potential high energy density and safety. However, this type of battery faces challenges such as volume expansion of electrode materials and poor interface contact during the charging and discharging process, resulting in poor cycle performance, which leads to battery performance degradation and shortened life. Traditional dry binders (such as polytetrafluoroethylene, PTFE) not only fail to meet the special needs of all-solid-state batteries, but also have a significant impact on the ecological environment during their manufacturing and processing.
[0003] Therefore, there is an urgent need to provide a new all-solid-state battery with good cycle performance. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing an all-solid-state battery. The all-solid-state battery prepared by the preparation method of the present invention has good cycle performance, for example, after 200 charge and discharge cycles, the corresponding capacity retention rate exceeds 80%, or even exceeds 85%.
[0005] A first aspect of the present invention provides a method for preparing an all-solid-state battery.
[0006] Specifically, a method for preparing an all-solid-state battery comprises the following steps:
[0007] Preparation of positive electrode sheet: Prepare positive electrode sheet using SIBS and positive electrode active material;
[0008] Preparation of negative electrode sheet: Prepare negative electrode sheet using SIBS and negative electrode active material;
[0009] Preparation of electrolyte membrane: SIBS and electrolyte are prepared to obtain electrolyte membrane;
[0010] Compressing and packaging the positive electrode sheet, the electrolyte membrane, and the negative electrode sheet to obtain the all-solid-state battery;
[0011] In the electrolyte membrane, the mass percentage of the SIBS is 3-10%.
[0012] SIBS is a poly(styrene-b-isobutylene-b-styrene) triblock copolymer in the form of a white powder and is an existing substance.
[0013] Preferably, during the preparation of the positive electrode plate, at least one of a solid electrolyte, a conductive agent and a current collector is used. Further preferably, a solid electrolyte, a conductive agent and a current collector are used simultaneously.
[0014] Preferably, the positive electrode active material is selected from at least one of lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide, lithium-rich layered oxide, spinel oxide, and LiFePO4; further preferably, the positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2).
[0015] Preferably, the solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte; further preferably, the solid electrolyte is a sulfide solid electrolyte.
[0016] Preferably, the sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11- a M 2-a P 1+a S 12 At least one of (M=Ge, Sn, Si, 0<a<2); further preferably, the sulfide solid electrolyte is Li6PS5Cl.
[0017] Preferably, the conductive agent is selected from at least one of SuperP (acetylene black), Ketjen black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; further preferably, the conductive agent is vapor-grown carbon fiber.
[0018] Preferably, in the positive electrode sheet, by mass percentage, the content of the positive electrode active material is 60-90%, the content of the solid electrolyte is 5-30%, the content of the conductive agent is 0.1-10%, and the content of the SIBS is 0.1-10%.
[0019] Further preferably, in the positive electrode plate, by mass percentage, the content of the positive electrode active material is 65-90%, the content of the solid electrolyte is 10-20%, the content of the conductive agent is 0.1-10%, and the content of the SIBS is 1-10%.
[0020] Preferably, in the positive electrode plate, the positive electrode active material is lithium nickel cobalt manganese oxide, with a content of 70% (mass percentage), the solid electrolyte is Li6PS5Cl, with a content of 26%, the conductive agent is vapor-grown carbon fiber, with a content of 3%, and the SIBS content is 1%.
[0021] Preferably, the preparation process of the positive electrode plate comprises the following steps:
[0022] The positive electrode active material, solid electrolyte, conductive agent and SIBS are mixed and stirred, and a solvent is added during the stirring process to adjust the viscosity of the slurry until a uniform slurry is formed, which is then coated on the current collector to form a positive electrode layer, and then vacuum dried and compacted to form a positive electrode sheet.
[0023] Preferably, the stirring speed is 100-2000 rpm; further preferably, the stirring speed is 1000-1500 rpm.
[0024] Preferably, the stirring time is 10-60 min; further preferably, the stirring time is 20-30 min.
[0025] Preferably, the solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isopentyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate, ethanol, glycol, acetonitrile and tetrahydrofuran; more preferably, the solvent is toluene.
[0026] Preferably, the vacuum drying temperature is 30-100°C; further preferably, the vacuum drying temperature is 40-50°C.
[0027] Preferably, the vacuum drying time is 6-24 hours; further preferably, the vacuum drying time is 10-24 hours.
[0028] Preferably, during the preparation of the negative electrode plate, at least one of a solid electrolyte, a conductive agent and a current collector is used. Further preferably, a solid electrolyte, a conductive agent and a current collector are used simultaneously.
[0029] Preferably, the negative electrode active material is selected from at least one of graphite, silicon and lithium titanate; further preferably, the negative electrode active material is silicon.
[0030] Preferably, the particle size of the silicon is 50 nm-5 μm; further preferably, the particle size of the silicon is 50-100 nm.
[0031] Preferably, the solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte; further preferably, the solid electrolyte is a sulfide solid electrolyte.
[0032] Preferably, the sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11-a M 2-a P 1+a S 12 At least one of (M=Ge, Sn, Si, 0<a<2); further preferably, the sulfide solid electrolyte is Li6PS5Cl.
[0033] Preferably, the conductive agent is selected from at least one of SuperP (acetylene black), Ketjen black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; further preferably, the conductive agent is vapor-grown carbon fiber.
[0034] Preferably, in the negative electrode plate, by mass percentage, the content of the negative electrode active material is 60-90%, the content of the solid electrolyte is 5-30%, the content of the conductive agent is 0.1-10%, and the content of the SIBS is 0.1-10%.
[0035] Further preferably, in the negative electrode plate, by mass percentage, the content of the negative electrode active material is 65-90%, the content of the solid electrolyte is 10-20%, the content of the conductive agent is 0.1-10%, and the content of the SIBS is 1-10%.
[0036] Preferably, in the negative electrode plate, the negative electrode active material is silicon, with a content of 60% (mass percentage), the solid electrolyte is Li6PS5Cl, with a content of 30%, the conductive agent is vapor-grown carbon fiber, with a content of 9%, and the SIBS content is 1%.
[0037] Preferably, the preparation process of the negative electrode plate comprises the following steps:
[0038] The negative electrode active material, solid electrolyte, conductive agent and SIBS are mixed and stirred, and a solvent is added during the stirring process to adjust the viscosity of the slurry until a uniform slurry is formed, which is then coated on the current collector to form a negative electrode layer, and then vacuum dried and compacted to form a negative electrode sheet.
[0039] Preferably, the stirring speed is 100-2000 rpm; further preferably, the stirring speed is 1000-1500 rpm.
[0040] Preferably, the stirring time is 10-60 min; further preferably, the stirring time is 20-30 min.
[0041] Preferably, the solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isopentyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate, ethanol, glycol, acetonitrile and tetrahydrofuran; more preferably, the solvent is toluene.
[0042] Preferably, the vacuum drying temperature is 30-100°C; further preferably, the vacuum drying temperature is 40-50°C.
[0043] Preferably, the vacuum drying time is 6-24 hours; further preferably, the vacuum drying time is 10-24 hours.
[0044] Preferably, the preparation process of the electrolyte membrane comprises the following steps:
[0045] The solid electrolyte and SIBS are mixed and stirred, and a solvent is added during the stirring process to adjust the viscosity of the slurry until a uniform slurry is formed, which is then coated on a substrate to form an electrolyte layer, and then vacuum dried and compacted to form an electrolyte membrane.
[0046] Preferably, the solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte; further preferably, the solid electrolyte is a sulfide solid electrolyte.
[0047] Preferably, the sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11- a M 2-a P 1+a S 12 At least one of (M=Ge, Sn, Si, 0<a<2); further preferably, the sulfide solid electrolyte is Li6PS5Cl.
[0048] Preferably, the stirring speed is 100-2000 rpm; further preferably, the stirring speed is 1000-1500 rpm.
[0049] Preferably, the stirring time is 10-60 min; further preferably, the stirring time is 20-30 min.
[0050] Preferably, the vacuum drying temperature is 30-100°C; further preferably, the vacuum drying temperature is 40-50°C.
[0051] Preferably, the vacuum drying time is 6-24 hours; further preferably, the vacuum drying time is 10-24 hours.
[0052] Preferably, the solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isopentyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate, ethanol, glycol, acetonitrile and tetrahydrofuran; more preferably, the solvent is toluene.
[0053] Preferably, in the electrolyte membrane, the content of the solid electrolyte is 90-99.5% and the content of the SIBS is 3-10% by mass.
[0054] Preferably, in the electrolyte membrane, the content of the solid electrolyte is 90-97% and the content of the SIBS is 3-10% by mass.
[0055] Preferably, the substrate is selected from copper foil, aluminum foil, glass plate, steel plate, PET substrate, PE substrate and products having a coating on the surface of the above materials; further preferably, the substrate is a PET substrate.
[0056] Preferably, in the process of preparing the positive electrode sheet, the negative electrode sheet and the electrolyte membrane, the SIBS is used in the form of SIBS colloid, and the SIBS colloid is formed by stirring and mixing SIBS with a dispersant.
[0057] Preferably, the dispersant is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isopentyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate, ethanol, glycol, acetonitrile and tetrahydrofuran; further preferably, the dispersant is toluene.
[0058] Preferably, during the preparation of the SIBS colloid, the stirring speed is 100-2000 rpm; further preferably, the stirring speed is 1000-1500 rpm.
[0059] Preferably, during the preparation of the SIBS colloid, the stirring time is 30-120 min; further preferably, the stirring time is 60-90 min.
[0060] Preferably, the solid content of the SIBS colloid is 1-10% (mass fraction), and more preferably 3-5%.
[0061] Preferably, the side of the dried electrolyte membrane coated with the material (i.e., the side of the substrate surface coated with the electrolyte and SIBS) is laminated with the side of the negative electrode plate coated with the material (i.e., the side of the current collector coated with the negative electrode active material), and then isostatic pressing is performed. After the treatment, the substrate of the electrolyte membrane is demolded to obtain a composite electrolyte-negative electrode layer.
[0062] The positive electrode sheet is attached to the other side of the electrolyte in the above electrolyte-negative electrode layer to form a positive electrode-electrolyte-negative electrode structure, which is then encapsulated in an aluminum-plastic bag and subjected to isostatic pressing to obtain an all-solid-state battery (i.e., an all-solid-state soft-pack battery cell).
[0063] A second aspect of the present invention provides an all-solid-state battery.
[0064] An all-solid-state battery is prepared by the above preparation method.
[0065] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0066] (1) In the preparation process of the all-solid-state battery described in the present invention, a specific SIBS with good elasticity is selected as a binder, and the content of SIBS in the electrolyte membrane is not less than 3%, which can effectively alleviate the volume expansion of the electrode during the charging and discharging process, reduce the pulverization and shedding of the electrode material, and maintain the stability of the electrode structure, thereby significantly improving the cycle stability of the all-solid-state battery. For example, after 200 charge and discharge cycles, the corresponding capacity retention rate exceeds 80%, or even exceeds 85%.
[0067] (2) The SIBS material used in the present invention is environmentally friendly and has application potential. The SIBS binder is easy to disperse and has high elasticity. The electrolyte membrane prepared by SIBS can maintain a high ionic conductivity on the basis of molding, and buffer the stress caused by the volume expansion from the electrode side during the cycle process, thereby ensuring the integrity of the solid-solid interface. DETAILED DESCRIPTION
[0068] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0069] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0070] The SIBS used in the following examples or comparative examples is a poly(styrene-b-isobutylene-b-styrene) triblock copolymer in the form of white powder, which is an existing material.
[0071] Example 1
[0072] A method for preparing an all-solid-state battery comprises the following steps:
[0073] The preparation process of the positive electrode sheet includes the following steps:
[0074] The positive electrode active material (lithium nickel cobalt manganese oxide, i.e. LiNi 0.8 Co 0.1 Mn 0.1 O2), solid electrolyte (Li6PS5Cl), conductive agent (vapor-grown carbon fiber) and SIBS were mixed and stirred at a speed of 1500 rpm for 30 min. During the stirring process, solvent toluene was added to adjust the slurry viscosity until a uniform slurry was formed, and then coated (coating amount was 20 mg / cm 2 ) A positive electrode layer is formed on the current collector copper foil, and a positive electrode sheet is formed by vacuum drying (temperature is 50°C, time is 24h) and compacting.
[0075] In the positive electrode sheet, the positive electrode active material is lithium nickel cobalt manganese oxide, with a content of 70% (mass percentage), the solid electrolyte is Li6PS5Cl, with a content of 26%, the conductive agent is vapor-grown carbon fiber, with a content of 3%, and the SIBS content is 1%.
[0076] The preparation process of the negative electrode sheet includes the following steps:
[0077] The negative electrode active material (silicon powder, particle size of 100nm), solid electrolyte (Li6PS5Cl), conductive agent (vapor-grown carbon fiber) and SIBS were mixed and stirred at a speed of 1500rpm for 30min. During the stirring process, solvent toluene was added to adjust the slurry viscosity until a uniform slurry was formed, and then coated (coating amount was 15mg / cm 2 ) A positive electrode layer is formed on the current collector copper foil, and a negative electrode sheet is formed by vacuum drying (temperature is 50°C, time is 24h) and compaction.
[0078] In the negative electrode sheet, by mass percentage, the negative electrode active material is silicon powder, with a content of 60%, the solid electrolyte is Li6PS5Cl, with a content of 30%, the conductive agent is vapor-grown carbon fiber, with a content of 9%, and the SIBS content is 1%.
[0079] The preparation process of the electrolyte membrane includes the following steps:
[0080] The solid electrolyte (Li6PS5Cl) and SIBS were mixed and stirred at a speed of 1500 rpm for 30 min. During the stirring process, solvent toluene was added to adjust the slurry viscosity until a uniform slurry was formed, and then coated (coating amount was 20 mg / cm 2 ) An electrolyte layer is formed on a PET substrate, and an electrolyte membrane is formed by vacuum drying (temperature is 50°C, time is 24h) and compaction.
[0081] In the electrolyte membrane, the content of the solid electrolyte is 97% and the content of the SIBS is 3% by mass.
[0082] The side of the dried electrolyte membrane coated with the material (i.e. the side of the substrate surface coated with the electrolyte and SIBS) is laminated with the side of the negative electrode plate coated with the material (i.e. the side of the current collector coated with the negative electrode active material), and then isostatic pressing is performed. After the treatment, the substrate of the electrolyte membrane is demolded to obtain a composite electrolyte-negative electrode layer. The positive electrode plate is laminated to the other side of the electrolyte in the above-mentioned electrolyte-negative electrode layer to form a positive electrode-electrolyte-negative electrode structure, and the whole solid-state battery (i.e., whole solid-state soft-pack battery cell) is obtained by encapsulating it in an aluminum-plastic bag and performing isostatic pressing.
[0083] Example 2
[0084] Compared with Example 1, Li7P3S 11 Instead of Li6PS5Cl in Example 1, the solid electrolyte Li7P3S 11 The content of is 90%, the content of SIBS is 10%, and the rest of the process is the same as in Example 1.
[0085] Example 3
[0086] Compared with Example 1, the difference of Example 3 is that in the process of preparing the positive electrode sheet, the negative electrode sheet and the electrolyte membrane, SIBS is used in the form of SIBS colloid, and the SIBS colloid is formed by stirring and mixing SIBS with dispersant toluene, the stirring speed is 1500rpm, and the stirring time is 90min. The solid content of SIBS colloid is 5% (mass fraction).
[0087] Comparative Example 1
[0088] In this comparative example, the conventional binder (PTFE) is used to replace the SIBS in Example 3 to prepare the positive electrode sheet, the negative electrode sheet, the electrolyte membrane and the all-solid-state soft-pack battery cell. The specific preparation process is as follows:
[0089] Preparation of composite positive electrode sheet:
[0090] a) In a glove box filled with argon, lithium nickel cobalt manganese oxide (LiNi0.8Co0.1Mn0.1O2), sulfide solid electrolyte (Li6PS5Cl) and conductive agent (vapor-grown carbon fiber) were manually ground in a mortar for 10 min at a certain mass ratio until they were uniformly mixed to obtain a composite positive electrode material;
[0091] b) The composite positive electrode material and the binder (polytetrafluoroethylene) are prepared by a solvent-free dry process.
[0092] Calculated by mass percentage, in the composite positive electrode sheet, the content of the positive electrode active material lithium nickel cobalt manganese oxide is 70wt.%, the content of the sulfide solid electrolyte Li6PS5Cl is 26.5wt.%, the content of the conductive agent vapor-grown carbon fiber is 3wt.%, and the content of the binder polytetrafluoroethylene is 0.5wt.%.
[0093] Preparation of solid electrolyte membrane:
[0094] The solid electrolyte membrane is made of sulfide solid electrolyte and polytetrafluoroethylene through a solvent-free dry process.
[0095] In the solid electrolyte membrane, the content of the sulfide solid electrolyte Li6PS5Cl is 99.5wt.%, and the content of polytetrafluoroethylene is 0.5wt.%.
[0096] Preparation of composite negative electrode sheet:
[0097] a) In a glove box filled with argon, the negative electrode active material silicon powder (particle size of 100 nm), the sulfide solid electrolyte Li6PS5Cl and the conductive agent vapor-grown carbon fiber were manually ground in a mortar for 10 min at a certain mass ratio until they were uniformly mixed to obtain a composite negative electrode material;
[0098] b) The composite negative electrode material and the binder are prepared by a solvent-free dry process to prepare a composite negative electrode sheet.
[0099] Calculated by mass percentage, in the composite negative electrode sheet, the content of negative electrode active material silicon powder is 60wt.%, the content of solid electrolyte Li6PS5Cl is 30wt.%, the content of conductive agent vapor-grown carbon fiber is 9wt.%, and the content of binder tetrafluoroethylene is 1wt.%.
[0100] Assembly of all-solid-state soft-pack batteries:
[0101] a) bonding the composite positive electrode sheet and the composite negative electrode sheet to the current collector copper foil by pressing;
[0102] b) placing the composite positive electrode sheet, the solid electrolyte membrane and the composite negative electrode sheet stack from bottom to top;
[0103] c) packaging the stacked sheets;
[0104] d) Pressing the packaged laminate to obtain a battery cell.
[0105] Comparative Example 2
[0106] Compared with Example 3, the difference of Comparative Example 2 is that the content of solid electrolyte in the electrolyte membrane of Comparative Example 2 is 98%, the content of SIBS is 2%, and the rest of the process is the same as that of Example 3.
[0107] Product effect testing
[0108] The production of the all-solid-state soft-pack battery in Comparative Example 2 failed because the dry electrolyte membrane could not be completely demolded after being transferred to the composite negative electrode plate, resulting in serious interface defects. The ionic conductivity of the Li6PS5Cl sulfide solid electrolyte is 3mS / cm, and the ionic conductivity of the electrolyte membrane prepared in Example 3 is 1.2mS / cm. In summary, a 3% content of the binder SIBS can ensure that a high ionic conductivity is maintained on the basis of complete demolding of the electrolyte membrane, so 3% is a more appropriate addition amount.
[0109] The conductivity of the dry electrolyte membrane prepared in Comparative Example 1 is 2.4mS / cm. Compared with the ion conductivity of Li6PS5Cl sulfide solid electrolyte of 3mS / cm, the conductivity of the electrolyte membrane in Example 3 and Comparative Example 1 has decreased. The reason is that the binder, as an inert component, has an unavoidable effect on the transmission of lithium ions, but the conductivity of the electrolyte membrane can still be maintained at ~mS level, indicating that both SIBS binder and polytetrafluoroethylene binder can be evenly dispersed in the electrolyte membrane, bonding the electrolyte particles together, and macroscopically manifested as a continuous electrolyte membrane.
[0110] The all-solid-state soft-pack battery cell prepared in Example 3 has a first-cycle 0.1C discharge specific capacity of 184.68 mAh / g, a first-cycle coulombic efficiency of 77.5%, and a capacity retention rate of 85% after 200 cycles at 0.3C.
[0111] The first cycle 0.1C discharge specific capacity of the all-solid-state soft-pack battery prepared in Comparative Example 1 is 192.35mAh / g, the first cycle coulomb efficiency is 80.7%, and the capacity is retained by 68% after 200 cycles at 0.3C. The difference in the first cycle performance is mainly due to the different overall impedance of the battery in Example 3 and Comparative Example 1, and the difference in the cycle performance is mainly because the high elasticity of SIBS can better alleviate the volume effect brought by silicon during the cycle process, so Example 3 shows a better capacity cycle retention rate.
[0112] In addition, the internal cross-section of the all-solid-state soft-pack battery cells prepared in Example 3 and Comparative Example 1 was observed after 200 cycles.
[0113] In the all-solid-state soft-pack battery cell prepared in Example 3, it can be observed that the positive and negative electrode structures are intact, without defects such as cracks and pores. This is due to the high elasticity of SIBS, which inhibits the electrode expansion during the cycle, allowing the electrode to remain intact. At the same time, it is also observed that the positive electrode / electrolyte interface and the negative electrode / electrolyte interface are intact without cracks. This is also due to the high elasticity of the SIBS binder, which can buffer the impact of electrode expansion on the electrolyte layer during the cycle, which is conducive to maintaining the integrity of the interface and reducing the interface impedance, so that the all-solid-state battery cell has good performance.
[0114] However, after the all-solid-state soft-pack battery cell prepared in Comparative Example 1 was cycled 200 times under the same conditions, obvious longitudinal cracks appeared on the negative electrode side. This was mainly because the stress caused by the volume effect caused by the de- / insertion of lithium in the silicon negative electrode could not be released during the long cycle. In addition, gaps were also clearly observed on the negative electrode / electrolyte interface, which was also caused by the volume effect of the negative electrode during the cycle.
[0115] In summary, SIBS can not only significantly improve the performance of all-solid-state soft-pack batteries, but is also environmentally friendly. Therefore, the present invention helps to realize the practical application of high-performance, safe and environmentally friendly all-solid-state batteries.
Claims
1. A method for preparing an all-solid-state battery, characterized in that: The following steps are involved: Preparation of positive electrode sheet: Prepare positive electrode sheet using SIBS and positive electrode active material; Preparation of negative electrode sheet: Prepare negative electrode sheet using SIBS and negative electrode active material; Preparation of electrolyte membrane: SIBS and electrolyte are prepared to obtain electrolyte membrane; Compressing and packaging the positive electrode sheet, the electrolyte membrane, and the negative electrode sheet to obtain the all-solid-state battery; In the electrolyte membrane, the mass percentage of the SIBS is 3-10%.
2. The preparation method according to claim 1, characterized in that: During the preparation of the positive electrode plate, at least one of a solid electrolyte, a conductive agent and a current collector is also used.
3. The preparation method according to claim 2, characterized in that: During the preparation of the positive electrode plate, a solid electrolyte, a conductive agent and a current collector are used simultaneously. In the positive electrode plate, the content of the positive electrode active material is 60-90% by mass, the content of the solid electrolyte is 5-30% by mass, the content of the conductive agent is 0.1-10% by mass, and the content of the SIBS is 0.1-10% by mass.
4. The preparation method according to claim 1, characterized in that: During the preparation of the negative electrode plate, at least one of a solid electrolyte, a conductive agent and a current collector is also used.
5. The preparation method according to claim 4, characterized in that: During the preparation of the negative electrode plate, a solid electrolyte, a conductive agent and a current collector are used simultaneously. In the negative electrode plate, the content of the negative electrode active material is 60-90% by mass, the content of the solid electrolyte is 5-30% by mass, the content of the conductive agent is 0.1-10% by mass, and the content of the SIBS is 0.1-10% by mass.
6. The preparation method according to claim 1, characterized in that: The preparation process of the electrolyte membrane comprises the following steps: The solid electrolyte and SIBS are mixed and stirred, and a solvent is added during the stirring process to form a slurry, which is then coated on a substrate to form an electrolyte layer, and the electrolyte membrane is formed through vacuum drying and compaction.
7. The preparation method according to claim 6, characterized in that: The solid electrolyte is selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte; and / or the solid electrolyte is a sulfide solid electrolyte, and the sulfide solid electrolyte is selected from Li7P3S 11 、Li3PS4、Li6PS5X、Li 11-a M 2-a P 1+a S 12 At least one of the following, wherein X=Cl, Br, I, M=Ge, Sn, Si, 0<a<2.
8. The preparation method according to claim 1 or 6, characterized in that: In the electrolyte membrane, the content of the solid electrolyte is 90-99.5% by mass, and the content of the SIBS is 3-10% by mass.
9. The preparation method according to claim 1, characterized in that: In the process of preparing the positive electrode sheet, the negative electrode sheet, and the electrolyte membrane, the SIBS is used in the form of SIBS colloid, and the SIBS colloid is formed by stirring and mixing SIBS with a dispersant, and the dispersant is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isopentyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate, ethanol, glycol, acetonitrile and tetrahydrofuran.
10. An all-solid-state battery, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Cited By
Gradient piezoelectric buffer layer, preparation method and solid-state battery
CN121983577A
